Zsákutcában. Töprengések az autó és a nagyváros egyre tragikusabban alakuló viszonyáról - Tiner, Tibor (Tér és Társadalom, 1989)
The present paper is a polemizing scientific essay which attempts at providing a comprehensive review of the intrinsic features of processes deeply bedded in the relationship between the car and the city. The author regards the metropolitan phenomena of motorization revolution as a crisis process of civilization. He argues against the present practice in which the headaches of metropolitan motor traffic are handled as problems requiring monofunctional solutions, albeit it is essentially linked to all functions of the city. The heavily expanded problems of urban motorization date back to a technocratic axiom from the heroic age of the automobile, fallacious from the beginning, according to which the city can be – or even, has to be – tailored to the scales of the car. With the rapidly increasing number of cars, the problems derived from this impossible principle have grown to threatening proportions, the quantitative change turned into a negative qualitative change. All this has greately distorted the relative balance which had earlier existed among urban functions, at least from the aspect of transport. The appearance of the railway was a shock to the city because it has transformed the urban structure in several ways and also triggered urban explosion. At the same time urban public transport also started to develop, which is, via its mass character, the only satisfactory way of meeting the needs of travelling within the city, mainly because it does not paralyse the other functions of the urban open space and is able to preserve this particular feature in harmony with city development, on the long run. The second shock to the city, which had much graver consequences than the first, was the motorization explosion (more precisely, the rapid headway of personal car traffic). Asserting the interests of individual transport, and their building into transport development concepts, resulted in a radical transformation of the texture of urban public areas. A complex erosion of the urban space started, a growing bleakness and decay, which also attacked the basis of urban existence and is diverting city life into a hazardous direction. There are two usual ways for cities to yield to the pressure of the car. The first is the sbcalled American way: i. e. the creation of cities at the scale of car, on huge areas, with no pedestrian traffic at all, with spatially dispersed city functions. The result: the city is dissolved within a huge, 'otherwise urbanized', space. Itsearlier essential feature, its human scale is disappearing completely. The second (the so-called European) way involves more suffering to the city, because a sharp conflict is evolving between the densely built-up historic city, tailored to pedestrians, and the spaceeating car. The conflict is usually solved to the benefit of the car not the city, mainly by 'hibrid' solutions, involving, on the one hand, attempts at realizing the city at the scale of the car (increasing space for transport on the surface) and preserving a human-scale city (diverting traffic under ground at high costs). But incomplete solutions do not satisfy either motor traffic or pedestrians, while urban public areas are increasing decaying. The major symptoms are: 1. increasing air pollution; 2. ever growing traffic noise; 3. increasing building damage; 4. ever deepening foil pollution; 5. hazardous environment overcharged with motor traffic; 6. motor crowdednessdue to 'space-eating' still traffic; 7. transformation of a growing percentage of urban public areas for the purposes of motor transport; increasing deformation of the urbanites' mentality and behaviour. The unique solution is viewed by the author in a gradual exclusion of individual car traffic from inner city areas and a significant reduction of speed limit. This is the only way to create a more human-faced urban life.